Land Use Planning on a Grand Scale: A Decision Maker’s Perspective - Harvey, E. (Maine Policy Review, 2010)
The author of this commentary, who served as a commissioner on the Maine Land Use Planning Commission (LURC) discusses the ground-breaking 400,000-acre concept plan by Plum Creek Corporation for development of the Moosehead Lake region in Maine. The highly-contested plan approved by LURC involves rezoning for hundreds of acres to allow for single family homes and resorts, and sets aside significant acreage in conservation.
Keywords: Maine Land Use Planning Commission; LURC; Plum Creek; Moosehead Lake; land use planning